Simplified bolted connection model for analysis of transmission line towers. (October 2020) - Balagopal, R.; Ramaswamy, Ananth; Palani, G.S.; Prasad Rao, N.
Abstract: Bearing type bolted connections are used in lattice structures such as lattice transmission line (TL) and communication towers for the connection between steel angle sections. These bolted connections play an important role in determining the deflection response of TL towers. The deflection predicted from analysis by using pin joint assumption for bolted connection is found to have variation of about 30 to 50% compared to the corresponding experimental results. Hence, there is a need to develop a comprehensive bolted connection model for accurate prediction of the deflection response of TL towers. In this paper, a simplified bolted connection model is proposed accounting for both axial and rotational stiffness for modeling bolted connections in lattice TL towers. The rotational stiffness accounting for slip due to eccentric load transfer in the bolted connections of steel angle section is formulated based on the relative translational deformation obtained from experimental studies at component level on lap joint made of two bolts in steel angle sections. Similarly, the axial stiffness is proposed based on load vs axial deformation response. The proposed model is validated for benchmark problems such as double diagonal plane truss and TL tower sub-assembly. Further, the proposed bolted connection model is also validated with experimental studies on two-dimensional king post truss and TL tower panel subjected to tensile loading. It is observed that the rotational stiffness accounting for slip is an important factor to be considered along with axial stiffness in the modeling of bolted connections of TL towers. Also, it is observed that the proposed bolted connection model helps in better prediction of the load-deformation response that are in close agreement with the corresponding experimental results and the variation is within 15%.